Combination of the Ilizarov Method and Intramedullary Fixation for the Treatment of Congenital Pseudarthrosis of the Tibia in Children: A Retrospective Observational Study - Yalikun, Ainizier; Yushan, Maimaiaili; Hamiti, Yimurang; Lu, Cheng; Yusufu, Aihemaitijiang (Frontiers in Surgery, 2022)
Abstract Purpose Congenital pseudoarthrosis of the tibia (CPT) is a rare disease in children and its treatment remains a challenge for orthopedic surgeons.The purpose of this study was to evaluate treatment outcome of patient with CPT treated by using Ilizarov method combined with intramedullary fixation. Method Eighteen patients were evaluated retrospectively from January 2009 to January 2020 were treated using Ilizarov method combined with intramedullary fixation.Demographic data ,clinical characteristics and complications were all recorded and investigated during period of follow-up. Ankle fuction was evaluated by the American Orthopaedic Foot and Ankle Society（AOFAS）ankle-hindfoot scores at last follow-up. Result All 18 patients with an average follow up of 39.2 months (25-85months) . The mean age was 6.2 years (3.5-11.2 years). Fourteen (77.8%) patients had primary bone union at site of pseudarthrosis, while 4 obtained union after secondary surgical intervention. The mean duration of Ilizarov was 8.1 months (4.2-13.5months).Eight (44.4%) patients had pin-tract infection during treatment. Four (22.2%) patients had proximal tibial valgus with a mean angle of 12.1°(5-25°), while seven (38.9%) patients had ankle valgus deformities with a mean of 10.3°(5-20°). Eleven (61.1%) patients had an average 1.4 cm of limb length discrepancy (LLD) (0.6-3.1cm) postoperatively.Five (27.8%) patients had refracture and recovered after a secondary surgery.At the last follow-up, the average postoperative AOFAS score was 72 (55-84). Conclusion Ilizarov method combined with intramedullary fixation is an effective method for the treatment of CPT, which can facilitate bony union and help to prevent refracture. Management of fibular pseudarthrosis is associated with functional outcomes. It is necessary to follow up until skeletal maturity and evaluate long-term clinical outcomes.